2015
DOI: 10.1186/s12879-015-1184-5
|View full text |Cite
|
Sign up to set email alerts
|

Improving hospital hygiene to reduce the impact of multidrug-resistant organisms in health care–a prospective controlled multicenter study

Abstract: BackgroundNosocomial infections are the most common complication during inpatient hospital care. An increasing proportion of these infections are caused by multidrug-resistant organisms (MDROs). This report describes an intervention study which was designed to address the practical problems encountered in trying to avoid and treat infections caused by MDROs. The aim of the HARMONIC (Harmonized Approach to avert Multidrug-resistant Organisms and Nosocomial Infections) study is to provide comprehensive support t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
5
0
1
Order By: Relevance
“…Strains were drawn from the national collection of the Robert Koch-Institute (RKI) to represent a broad spectrum of strains from different hosts that are prevalent in Germany, and from a collection of regional strains from northeastern Germany (HICARE Study) (Table 1) [23]. Methicillin-sensitive Staphylococcus aureus (MSSA) ATCC 6538 was used as the reference strain.…”
Section: Methodsmentioning
confidence: 99%
“…Strains were drawn from the national collection of the Robert Koch-Institute (RKI) to represent a broad spectrum of strains from different hosts that are prevalent in Germany, and from a collection of regional strains from northeastern Germany (HICARE Study) (Table 1) [23]. Methicillin-sensitive Staphylococcus aureus (MSSA) ATCC 6538 was used as the reference strain.…”
Section: Methodsmentioning
confidence: 99%
“…A study reported significant inter-hospital variations in length of stay due to infections, and a shorter stay was found in hospitals with good hygiene [89]. Good hospital hygiene management reduces microbial colonisation and thus reduces the risk of hospital-acquired infections caused by multi-drug resistant organisms, which are the most common complication during inpatient hospital care [90]. For patient factors, hospitalised patients are more likely to be elderly, severely ill, and have more comorbidities and these were also found to be constituents with prolonged length of stay [91].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The evaluation was integrated in HARMONIC (Harmonized Approach to avert Multidrug-resistant Organisms and Nosocomial Infections), an 2-years investigation study (2012-2014) of the implementation of a standardized MDRO-hygienic management in six acute care hospitals in the "Health Region Baltic Sea Coast" in Mecklenburg-Western-Pomerania in Northeast Germany. The detailed study protocol has been published elsewhere (Gerlich et al, 2015).…”
Section: Methodsmentioning
confidence: 99%